2019
DOI: 10.3390/cells8010018
|View full text |Cite
|
Sign up to set email alerts
|

mTOR: A Cellular Regulator Interface in Health and Disease

Abstract: The mechanistic target of Rapamycin (mTOR) is a ubiquitously-conserved serine/threonine kinase, which has a central function in integrating growth signals and orchestrating their physiologic effects on cellular level. mTOR is the core component of differently composed signaling complexes that differ in protein composition and molecular targets. Newly identified classes of mTOR inhibitors are being developed to block autoimmune diseases and transplant rejections but also to treat obesity, diabetes, and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 213 publications
(237 reference statements)
1
110
0
Order By: Relevance
“…Indeed, elevated mTOR activity has been reported in IBD patients, and mTOR inhibitors have been shown to be effective in IBD . Loss of function of autophagy can lead to misregulation of ROS, resulting in defects in mucin accumulation . In support, we showed that ROS and the autophagy inducer such as mTOR inhibitor induced mucin secretion in IECs, but an autophagy inhibitor or ROS scavenger inhibited mucin production in IECs.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, elevated mTOR activity has been reported in IBD patients, and mTOR inhibitors have been shown to be effective in IBD . Loss of function of autophagy can lead to misregulation of ROS, resulting in defects in mucin accumulation . In support, we showed that ROS and the autophagy inducer such as mTOR inhibitor induced mucin secretion in IECs, but an autophagy inhibitor or ROS scavenger inhibited mucin production in IECs.…”
Section: Discussionsupporting
confidence: 67%
“…3.1 mTORC1 [97,99] The Mammalian target of rapamycin complex I (mTORC1) controls growth and metabolism in response to nutrients, energy and redox status. The mTORC1 complex consists of the mTOR kinase, the core subunits Raptor and mLST8, and the PRAS40 and DEPTOR inhibitory subunits.…”
Section: Type 2 Diabetes -Mtorc1-centric Unifying Paradigmmentioning
confidence: 99%
“…In line with that, TSC1,2 knockout and constitutive RagA.GTP result in constitutive activation of mTORC1 under fasting conditions. mTORC1 controls growth and metabolism by phosphorylating and/or affecting its downstream targets S6K1, 4EBP, CRTC2, lipin, ATF4, HIF1a, PPARg, PPARa, ULK1, TFEB and others [97,99]. Phosphorylation of S6K1 and 4EBP results in ribosome biogenesis and in initiating CAP-dependent mRNA translation.…”
Section: Type 2 Diabetes -Mtorc1-centric Unifying Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mTORC1 and mTORC2 contains mLST8/GβL and DEPTOR, while mTORC1 also contains PRAS40 and Raptor, and mTORC2-specific components include rapamycin-insensitive component of mTOR (Rictor), mSin1, and Protor-1/2 [40,92]. mTOR complexes regulate growth, metabolism, autophagy cell death and mRNA translation [93,94].…”
Section: Dr and Mtormentioning
confidence: 99%